Perceptions of social studies teachers and fourth year students in social studies instructions in Lungsodaan Barangay High School - Alibangbang, Vicenta Cuadra 1946- (1978)
This study is on the perceptions of social studies teachers and fourth year students on social studies instruction in Lungsodaan Barangay High School in relation with the other academic subjects. Fifty three seniors of both sexes and 3 high school teachers of the discipline were served as respondents. The writer used the descriptive method in gathering the data.